THE COMPARISON BETWEEN ACCURACY OF CAPITAL ASSETS PRICING MODEL (CAPM) AND ARBITRAGE PRICING THEORY (APT) IN STOCKS INVESTMENT ON EXCHANGE NATIONAL PRIVATE BANKING LISTED ON INDONESIAN STOCK EXCHANGE - Laia, Kristin; Saerang, Ivonne (Universitas Sam Ratulangi, 2015)
There are two models of equilibrium that is still used as a matter of debating regarding accuracy in predicting the expected returns. Both of these models are the Capital Asset Pricing Model (CAPM) and the Arbitrage Pricing Theory (APT). This research was conducted to determine the accuracy of each model in predicting the expected returns and to know which model is the most accurate in predicting expected returns on the exchange national private banking. The population used is the exchange national private bankÂ that is in the directory of Bank Indonesia and there were 35 banks. After purposive sampling stage, the sample used is worth as much as 15 banks. The accuracy of each model are known by paired samples t-test. As for knowing the most accurate model is to calculate the standard deviation from the results of ERI from each model. The results showed that the APT model with three macroeconomic factors more accurate in predicting expected returns of stock on the exchange national private banking. So, investors in theÂ exchange national private bankingÂ should use the APT model to predict the expected return. Keywords: CAPM, APT, actual return, expected return, general banking, foreign exchange